Health Program Management Factors Related to Budget Realization at the Kolaka District Health Office - akbar, muhammad ikhsan; Risky, Sartini; Saafi, La Ode; Asri, Andi (YCAB Publisher, 2025)
Objective: The purpose of this study was to analyze the Health Program Management Factors Associated with Budget Realization at the Kolaka District Health Office. Methods: This research is a quantitative study, with a case-control study design. The population is 13 Health center and the Kolaka District Health Office with a total sample of 209 people, simple random sampling technique Results: The results of statistical tests showed that there is a relationship between planning and budget realization, the Chi-Square value is 71.980 and Phi value of 0.601 with range between 0.60-0.799, which means that there is a strong relationship. And there is relationship between government regulations and Budget Realization, it is known that the Chi-Square value is 49.689and Phi value of 0.501 with range between 0.40-0.599, which means there is a medium relationship. Conclusion: There is a relationship between Health Program Management Factors and Budget Realization at the Kolaka District Health Office.